(3JPcQI GdeHJOis - (3YHO GdQMje Hf GdMSjf Hf YHO GdQMef, CHh GdaVd, Rjf GdOjf, GdMGaX GdYQGbj, J (B806 (3g`s ((3JLGg GdcYHI HecI s)
(3ChdgG (B:s
(3ef HYO MeO Gddg Pi GdBdGA agPg GdebGUO GdegeI JhVM ef Yde GdMOjK QSeg fXeJg JHUQI ddeHJOi hJPcQI ddefJgi s
(3BNQgG (B:s
(3hcedJ HWjHI GdejehfI aQRJ ef LOQgG eUhfg s
(3HgG fXGe GdJYbjHIs
(3hYdjgG GLGRGJ hSeGYGJs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B344 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B204s
Keywords: (3eJaQbGJs